TBL2 Promotes Tumorigenesis via PRMT5/WDR77‐Mediated AKT Activation in Breast Cancer - Xiuqing Lu; Chao Zhang; Lewei Zhu; Sifen Wang; Lijun Zeng; Wenjing Zhong; Xuxia Wu; Qi Yuan; Hailin Tang; Shien Cui; Yeru Tan; Yuehua Li; et al. (Advanced Science)
Abstract Breast cancer (BC) is a common malignancy that affects women worldwide. Although transducing beta‐like 2 (TBL2), a member of the WD40 repeat protein family, has been implicated in various intracellular signaling pathways, its precise function in BC remains unclear. The expression of TBL2 is analyzed using real‐time PCR, western blotting, and immunohistochemistry in BC patient specimens. Kaplan–Meier survival analysis is employed to assess its prognostic significance. Proteomic analysis, immunoprecipitation tests, and protein immunoblotting are employed to examine the impact of TBL2 on AKT phosphorylation activation. The findings reveal selective overexpression of TBL2 in BC, correlating significantly with various clinicopathological characteristics and poor survival outcomes in patients with BC. Through in vivo and in vitro experiments, it is observed that TBL2 suppression inhibits BC cell proliferation, while TBL2 overexpression has the opposite effect. Mechanistically, TBL2 is identified as a scaffolding protein that promotes PRMT5 and WDR77 interaction. This interaction enhances the methyltransferase activity of PRMT5, leading to increased AKT phosphorylation activation and promotion of breast cancer cell proliferation. In conclusion, this study uncovers a novel function of TBL2 in the activation of AKT by PRMT5 and suggests TBL2 as a potential therapeutic target for BC treatment.